A note on public debt, tax-exempt bonds, and Ponzi games - Wigger, Berthold U. (IMF [Washington]US, 2007)
Demonstrates that government can run a Ponzi game if the economy without public debt is dynamically efficient. This becomes possible when the return on private bonds or equity is taxed and the government issues tax-exempt bonds. Notes that unlike a traditional Ponzi game, the welfare effects of a Ponzi game based on the issuance of tax-exempt bonds are rather mixed.